The correlation of head posture (NSL/OPT angle) with maxilla and mandible relation (ANB angle) by cephalometric analysis (Review of Deutro Malay children aged 10–12 years in Jakarta) - Putri, Annisa Galuh Rahmawati Hendra; Budiardjo, Sarworini B.; Suharsini, Margaretha (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Proper head posture involves an upright head with minimal muscle work and maximum mechanical efficiency in the central nervous system. Muscular imbalance in the cervical spine and stomatognathic system affects head posture and maxillary–mandibular malrelation. Age 10–12 years is the golden period for orthodontic treatment, for which an assessment of head posture needs to be considered. The nasion-sella line/odontoid process tangent (NSL/OPT) angle represents flexion–extension of the head posture; the A point, Nasion, B point (ANB) angle is used to determine the maxillary–mandibular relationship. No research has ever been conducted on the relationship between the NSL/OPT and ANB angles in children of the Deutro Malay race aged between 10 and 12 years. Purpose: This study aims to analyze the relationship between the NSL/OPT and ANB angles in children of the Deutro Malay race aged between 10 and 12 years. Methods: This research was conducted at the Pediatric Dental and Radiology Clinic of Universitas Indonesia Dental Hospital with 33 respondents aged between 10 and 12 years, taking the inclusion and exclusion criteria into account. Lateral cephalometric radiographs were taken, and the NSL/OPT and ANB angles were determined using ImageJ software. Data analysis was conducted using the Pearson correlation test. Results: The mean values for the NSL/OPT and ANB angles are 97.9 and 3.15, respectively. The correlation test result (r = 0.067; p-value = 0.713) indicates an immensely weak relationship between the NSL/OPT and ANB angles and is not significant. Conclusion: The results demonstrated that there was an exceedingly weak linear relationship; it can be concluded that the angle of head posture cannot be correlated to the ANB angle.